PENGARUH CITRA MEREK DAN PERSEPSI KUALITAS TERHADAP NIAT PEMBELIAN ULANG DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING DI COFFEE SHOP “KARAKTER KOPI” DENPASAR - Kadek Silvia Natasya Febriyanti (Majalah Ilmiah Widyacakra, 2020)
ABSTRACTThis research is based on the researcher's interest in the development and competition of thegrowing coffee shop business in the present era where Brand Image, Quality Perception,Customer Satisfaction, and Repurchase Intention are very important in the development ofthis business. The purpose of this study is to determine the indirect effect of brand image onrepurchase intentions through customer satisfaction and perceived quality of repurchaseintentions through customer satisfaction. The data used in this study are primary dataobtained from the results of distributing questionnaires to respondents "Coffee Character".The sampling technique uses purposive sampling method. The criteria used are "CoffeeCharacter" consumers who have made purchases more than once. The number of samples inthis study amounted to 100 respondents. Data analysis method used in this research is pathanalysis using software with SPSS 23.0 for Windows. This study uses the Sobel Test todetermine the mediation hypothesis. The results of this study indicate that the influence ofcustomer satisfaction mediates the effect of brand image on repurchase intentions and theinfluence of customer satisfaction mediates the effect of perceived quality on repurchaseintentions.